TEACHING THE HUMOROUS TEXTS IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOM: EFL Classroom - Rochmawati, Dyah (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2011)
Humor is an important tool to achieve certain purposes. Humor is at first a type of language behavior. Even though humor, as a linguistic and interactional process, appears to be a universal human phenomenon, it is more obviously embedded in situated socio-cultural context than most other communication. Humor is a (socio)linguistic and sociocultural phenomenon which has a wide range of instructional values. Humorous texts are a reading material in EFL classroom in Indonesia. Discourse analysis has recently begun to explore humor in discourse from both the linguistic and socio-cultural perspective. The present paper addresses how to present and analyze the humorous texts taken from the Reader’s Digest magazine in EFL classroom which covers (1) the structure and the linguistic devices of humor discourse, (2) the pragmatics and cultural content of humor discourse, and (3) how to present the humorous texts in EFL classroom.